Supply chain management skills to sense and seize opportunities. Issue 2 (8th May 2017) - Tatham, Peter; Wu, Yong; Kovács, Gyöngyi; Butcher, Tim
Abstract : Purpose: The purpose of this paper is to investigate the supply chain management (SCM) skills that support the sensing and seizing of opportunities in a changing business environment. Design/methodology/approach: Based on the previous literature on the T-shaped model of SCM skills, data were collected through a mail survey among Australian business executives. The resultant skill sets are grouped along factors that support the sensing vs seizing of opportunities. Findings: Interestingly from an SCM perspective, functional logistics-related skills are important to maintain competitiveness but are not the ones contributing to a firm's ability to sense opportunities and threats, and to seize opportunities in a changing business environment. The authors, therefore, support the notion that supply chain managers should be managers first. Factual SCM knowledge is the solid basis, but otherwise only an entry requirement in this field. Research limitations/implications: Problem-solving skills, along with forecasting and customer/supplier relationship management, stand out as important components that support the ability of supply chain managers to sense and shape opportunities and threats in a turbulent business environment. This focus would tend to suggest the importance of supply chain integration and collaboration as management approaches. Other SCM skills from warehousing and inventory management to transportation and purchasing are more prevalent for maintaining competitiveness. Practical implications: The results of the survey and the consequential analysis indicate that the content of tertiary-level educational programmes should be significantly reviewed to deliver two distinct (but partially overlapping) streams that focus on the generalist and functionalist managers who must work together in the management of the increasingly global and complex supply chains. Social implications: Functional skills often form the basis of training and education programmes for supply chain managers. Whilst these form the solid foundation for their jobs, they are entry requirements at best. In a changing business environment, other skills are needed for success. Given that turbulence is becoming the norm rather than the exception, this finding necessitates rethinking in training and education programmes, as well as in the recruitment of supply chain managers. Originality/value: Testing the T-shaped model of SCM skills from a dynamic capabilities perspective, the results of the factor analysis lead to a regrouping of skill sets in terms of sensing and seizing opportunities in a turbulent business environment.